Converting industrial noise into useful electrical energy: a review and case study on acoustic energy harvesting in district cooling plants - Zurina, Ismaili; Mohamad Asrul, Mustapha; Mohammad Omar, Abdullah; Gaddafi, Ismaili; Amira Satirawaty, Mohamed Pauzan (Springer Nature, 2025)
Acoustic energy harvester (AEH) studies are commonly applied in the transportation sector, often overlooking industrial areas despite their substantial contribution to noise pollution in surrounding neighbourhoods. Furthermore, AEH approaches are primarily experimental and less common in real-world applications due to the signifcant knowledge gap in applying AEH systems for industrial noise. Therefore, this paper provides a comprehensive review of the latest advancements in AEH system, development aiming to convert industrial noise into useful electrical energy. Subsequently, this paper presents a case study demonstrating the feasibility of converting industrial noise from district cooling plant into useful electrical energy for powering small electronic devices. The case study result shows that noise mapping of the district cooling plant indicates that the chiller generates a continuous sound level approximately 91 to 96 dB, making it suitable for powering electronic devices within the chiller plants. Additionally, the fndings reveal a notable voltage output of 0.0258 V from the AEH system, achieved using the LDT1-028 K PT piezo flm.